Detecting the body’s reproductive hormonal brake against tissue overgrowth: Micrin/SgII-70 - John E. Hart; Keith G. Davies; Christopher R. Mundy; Aurelia C. Hart; David R. Howlett; Russell P. Newton (PLoS ONE, 2026)
A new humoral factor has been detected, within a project aiming to disclose the body’s reproductive hormonal brake against tissue overgrowth, micrin (‘my-crin’). Factor purification involved fractionation of ovine and bovine ovarian follicular fluid and blood plasma and serum, with evaluation via rat bioassays in vivo and in vitro. Analysis averse, the molecular effector provided a chemical conundrum. Evidence from mass spectrometry (MS) is problematic, with spectra from MALDI-TOF, the only productive MS modality, confused by a target polypeptide exhibiting artefacts during processing, storage and MALDI set-up in terms of C-terminal truncation and water losses, along with dimerization (C-terminally truncated fragments doubled up). Evidence from chemical sequencing of amino acid (aa) residues is likewise confusing, but consistent with a spiralised depolymerisation within the Edman reaction chamber of a unitary polypeptide. Data decryption has overcome molecular intractability, supported by the results of tryptic digestion and epitope mapping using immunohistochemistry (IHC). The detected inhibitory factor relates to secretogranin II (SgII), the neurosecretory prohormone, in the form of a secreted acidic 70-aa polypeptide derivative called here SgII-70 (‘sig two seventy’). The product of peptide splicing, micrin/SgII-70 is a twisted amphipathic molecule, with ends entwined (via salt bridging), the complex knotted structure confounding Edman and MALDI analyses, as well as computational molecular modelling, whilst conferring protease and heat resistance. Hexapeptide mimetics simulating both ends of the hormone together have been demonstrated in different species and settings in antiorganotrophism (tissue reduction via fewer, smaller cells) and reproductive modulation (more offspring). There are potential clinical applications for agonists in tissue overgrowth conditions such as endometriosis, PCOS, BPH and cancer, and for micrin antagonists in infertility.